Insights from and future directions for a nationwide science and engineering education collaboration in stratospheric ballooning - Covitt, Beth A.; Des Jardins, Angela C.; Agrimson, Erick P.; Ash, Jason T.; Bailey, Sean C.C.; Barber, Katelyn A.; Bastidas, Mike J.; Bering, Edgar A.; Bernards, Matthew T.; Choi, Anthony; Conklin, Nicholas B.; Do, Jacqueline K. Q.; et al. (Frontiers in Astronomy and Space Sciences, 2026)
The Nationwide Eclipse Ballooning Project (NEBP) engaged 53 teams of students from across the United States to fly experiments on high-altitude balloons for the 2023 annular and 2024 total solar eclipses. By many measures, NEBP was a successful project. However, the teams did encounter challenges. To better understand what could be improved for similar future projects, this study engaged project partners in examining strengths, challenges, and recommendations across four topics: project structure, education and research approach, broadening participation, and funding. Analysis of the topics was completed through written comments followed by remote focus group discussions. The project director and evaluator then synthesized the written and focus group comments to provide the results shared here. Identified strengths included a project structure facilitating regional-scale collaboration within a national network and a focus on providing undergraduate students with innovative, mission-based experiences. Partners also identified challenges including, for example, making in-depth engagement with analyzing project data and drawing scientific conclusions accessible to undergraduate students. Key recommendations include the need for real-world interdisciplinarity, a leadership group that reflects team types, a robust communication platform used at all levels, a modular approach for participation levels and time lengths, and flexibility in funding choices.